Investigations into the behavior, detection, and mitigation of oil in a sea ice environment - Desmond, Durell (2024)
The Arctic is warming at a rate of three times the global average, and projections warn that the average surface Arctic Ocean temperature may increase by 3 °C by 2100. Due to this Arctic warming, there have been steady decreases in sea ice extent and thickness. In particular, the Arctic has lost much of its multi-year ice (MYI) (i.e., ice that survives multiple summers) and is dominated by first-year ice (FYI) (i.e., ice that grows in the winter but melts in the summer). FYI is more saline than MYI and therefore has a lower albedo, thereby increasing the input of solar radiation into the ice-ocean system by 50%. Further Arctic amplification is caused by the thinning and reduction of snow cover and the occurrence of a longer open water season. A direct consequence of this Arctic warming is an increased interest in oil exploration, extraction, and transport, owing to the greater feasibility, which increases the likelihood of a potential oil spill in the marine environment. Notably, spillage by either an oil tanker or an underwater pipeline poses the biggest threat to the Arctic environment and its inhabitants. In order to combat this threat, the establishment of viable oil detection and mitigation techniques suitable for Arctic environments are currently in development. This urgency has led to the conduction of several oil-in-ice experiments to study various aspects of oil spill preparedness. The research herein aims to build on past work with a focus on oil behavior (i.e., migration tendencies, encapsulation potential, partitioning within sea ice, evaporation, dissolution, photooxidation, biodegradation), detection (i.e., radar), and mitigation (i.e., bioremediation) in sea-ice environments. This research consists of data collected from two artificial oil-in-ice mesocosm experiments in which microbial analyses (community composition), physical analyses (X-ray, temperature, salinity, brine volume), chemical analyses (oil dielectrics, infrared spectroscopy, gas chromatography–mass spectrometry), and ...